Systematic Investigation of the Photopolymerization of Imidazolium‐Based Ionic Liquid Styrene and Vinyl Monomers. Issue 20 (9th September 2018) - Whitley, John W.; Jeffrey Horne, William; Shannon, Matthew S.; Andrews, Mary A.; Terrell, Kelsey L.; Hayward, Spenser S.; Yue, Shuwen; Mittenthal, Max S.; O'Harra, Kathryn E.; Bara, Jason E.
ABSTRACT: The use of ionic liquids (ILs) as media in radical polymerizations has demonstrated the ability of these unique solvents to improve both reaction kinetics and polymer product properties. However, the bulk of these studies have examined the polymerization behavior of common organic monomers (e.g., methyl methacrylate, styrene) dissolved in conventional ILs. There is increasing interest in polymerized ILs (poly(ILs)), which are ionomers produced from the direct polymerization of styrene‐, vinyl‐, and acrylate‐functionalized ILs. Here, the photopolymerization kinetics of IL monomers are investigated for systems in which styrene or vinyl functionalities are pendant from the imidazolium cation. Styrene‐functionalized IL monomers typically polymerized rapidly (full conversion ≤1 min) in both neat compositions or when diluted with a nonpolymerizable IL, [C2 mim][Tf2 N]. However, monomer conversion in vinyl‐functionalized IL monomers is much more dependent on the nature of the nonpolymerizable group. ATR‐FTIR analysis and molecular simulations of these monomers and monomer mixtures identified the presence of multiple intermolecular interactions (e.g., π–π stacking, IL aggregation) that contribute to the polymerization behaviors of these systems. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2364–2375 Abstract : Styrene‐based ionic liquid (IL) monomers photopolymerize much more rapidly and completely than vinyl‐based IL monomers and conventional organic monomers. However, styrene‐based IL monomers are also subject to autopolymerization, which although problematic for storage does reveal that the resultant bulk poly(IL) materials have interesting shape‐memory and self‐healing properties. The photopolymerization efficiency of vinyl‐based IL monomers can be improved by increasing the size/length of the non‐polymerizable group to promote aggregation.